Response reaction of Deschampsia antarctica Desv. plants to UV-B irradiation and oxidative stress - Taran, N. Yu.; Okanenko, A. A.; Batsmanova, L. M.; Svetlova, N. B. (Ukrainian Antarctic Journal, 2009)
The effect of stress factors – ultraviolet radiation (UV-B) and hydrogen peroxide (H2O2) upon two species of Deschampsia plants – D. antarctica and D. caespitosa were studied. Investigations performed with D. antarctica plant samples delivered of Antarctic and D. caespitosa from Carpathian Mountains showed that UV-B radiation caused changes mainly pigment composition - chlorophyll a and almost all (except violaxanthin) carotenoids. Lipid composition was characterized by accumulation of triacylglicerols, sulphoquinovosyl diacylglycerol and phopsphatydylcholine while monogalacto-syldiacylglycerol quantity decreased. H2O2 treatment cause increase chlorophyll a content in both species and carotenoids in D. antarctica plants. Concerning glycolipid composition one could see monogalactosyldiacylglycerol content decrease in D. caespitosa whereas only insignificant SQDG enlargement was noted in D. antarctica leaves.